Examining risk factors for overweight and obesity in children with disabilities: a commentary on Bronfenbrenner's ecological systems framework. (4th July 2019) - Walker, Meaghan; Nixon, Stephanie; Haines, Jess; McPherson, Amy C.
ABSTRACT: Globally, overweight and obesity (OW/OB) levels are high among children, with rates surpassing the adult population. With such high pediatric OW/OB rates, it is imperative that risk factors are identified and explored. Thus, Davison and Birch developed an adapted framework, based on Bronfenbrenner's Ecological Systems Theory, which identifies and categorizes the factors in a child's life that put them at risk for OW/OB. While a socioecological perspective has been a useful tool for examining risk factors in typically developing pediatric populations, this holistic approach has not yet been applied to populations of children with disabilities, who are at an even higher risk of OW/OB than their typically developing peers. This commentary, therefore, explores Bronfenbrenner's Ecological Framework as applied to OW/OB by Davison and Birch, and critically examines its application to children with disabilities.